Postdebriefing Supervised Practice Improves Clinical Performance During Simulation-Based Cardiopulmonary Resuscitation Encounter. - Paloncy, Kristin Ann (Athletic Training Education Journal (Allen Press Publishing Services Inc.), 2020)
Context: Simulation is commonly incorporated into medical and health programs as a method of skill practice and evaluation and can be effective at improving athletic training student learning outcomes when purposefully designed. Objective: The purpose of this study was to determine what level of impact participation in supervised practice after debriefing within a simulation-based cardiovascular emergency scenario using the Laerdal SimMan in a university simulation center in the United States had on athletic training students' clinical performance. Design: Quantitative quasi-experimental cohort design with repeated measures study. Patients or Other Participants: Convenience sample of undergraduate athletic training students (n = 46) enrolled in a professional program at a university in the Midwest. Intervention(s): Participation in supervised practice of cardiopulmonary resuscitation skills after debriefing in a simulation. Main Outcome Measure(s): Clinical competency with associated cardiopulmonary resuscitation skills using the Laerdal Learning Application software program that interfaces with the simulation hardware. Results: There was a statistically significant interaction between groups (F1,10 = 18.70, P > .05, g = 652) indicating participants in the supervised practice after debriefing group were significantly higher (mean = 0.72, SD = 0.05) than those that did not have supervised practice after the debriefing (mean = 0.17, SD = 0.05). Conclusions: The design and development of a simulation experience is optimized when there is deliberate consideration of what components and exposure to these learning components will lead to certain outcomes. Even though supervised practice after debriefing has been identified as optional for skill-based simulations, the current study demonstrates that the supervised practice of clinical skills component is vital within emergency cardiovascular simulation encounters for participants to increase clinical competency.